Genomic sequencing effort for SARS-CoV-2 by country during the pandemic. (February 2021) - Furuse, Yuki
Highlights: How various countries have performed in sequencing of SARS-CoV-2 was evaluated. We assessed performance from the perspectives of "fraction", "timeliness", and "openness". USA, Iceland, Netherlands, UK, and Australia showed great performance. Good performance for some low- and middle-income countries was also observed. Abstract: Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), tremendous efforts have been made to sequence the viral genome from samples collected throughout the world. Here, we evaluate how various countries have performed in sequencing from the perspectives of "fraction", "timeliness", and "openness". We found that high proportions of samples were sequenced in the UK, the USA, Australia, and Iceland; sequencing was performed promptly in Iceland, the Netherlands, and the Democratic Republic of the Congo; and data were shared timely from the Netherlands, the USA, Iceland, and the UK. Although many developing countries have high numbers of SARS-CoV-2 infected cases but few published sequences, we observed good performance on sequencing efforts for some low- and middle-income countries. Further strengthening of the sequencing capacity at a global level would help in the fight against not only the current pandemic but also future outbreaks of viral diseases.